PENGARUH KESADARAN HUKUM MAHASISWA TERHADAP KEPATUHAN HUKUM TENTANG PERATURAN PERUNDANG-UNDANGAN PLAGIASI TERKAIT KARYA TULIS ILMIAH - Khoiruddin Manahan Siregar (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2023)
The fact that IIPA (Imternational Intellectual Property Alliance) launched shows a decrease in plagiarism violations to the Watchlist from the previous 2003 access in the Watchlist category. This false rejection is most effective because law number 20 of 2003 concerning the national education system article 25 paragraph 2 and article 70 regulates sanctions for those who commit plagiarism, especially people who are in the educational environment. Usually, the maximum law-abiding society comes from among highly educated people consisting of students. The application of behaviors and ideologies tends to decline from higher levels to lower levels. This research uses quantitative methods with a descriptive and explanatory approach, which describes more than a few variables that are admired with complexity and units under which they are observed and explains the relationship, influence or difference between one variable and every other variable. The population in this review, students of the Constitutional Law Study Program, Faculty of Sharia and Legal Sciences, Syekh Ali Hasan Ahmad Addary State Islamic University, Padangsidimpuan in the even semester of 2022. The sample in this observation became 100 people. The findings of observations show that legal awareness of legal compliance has a significant and positive influence.